VD_FINDINFO Arrêt / 2015 / 1057 vom 8. Dezember 2015 - VD Tribunal cantonal (2015)
LOI FÉDÉRALE SUR L'ASSURANCE-INVALIDITÉ, AIASSURANCE, RENTE D'INVALIDITÉ, MESURE D'ORDRE PROFESSIONNEL, COMPARAISON DES REVENUS | 14a LAI, 17 LAI, 28 LAI, 4 LAI, 8 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 LPGA